Future of Apple: Business and Financial Analysis - Meng, Xiang (Transactions on Economics, Business and Management Research, 2024)
The technology industry has profoundly impacted the global economy by driving economic growth, creating employment opportunities, and promoting globalization. This article provides a strategic and financial analysis of Apple Inc., focusing on its market position, competitive advantage, and financial condition. Through a detailed SWOT analysis, this study emphasizes Apple’s strengths, including a strong brand image and continuous innovation, while pointing out its weaknesses, such as excessively high product pricing. The analysis identified growth opportunities in emerging markets and discussed the threats of intense competition. In terms of finance, this article studied key indicators: profitability ratio (net profit margin and operating profit margin), liquidity ratio (current ratio and quick ratio), and solvency ratio (debt to equity ratio and interest coverage ratio). The research results indicate that despite facing challenges in liquidity and market competition, Apple has maintained strong profitability and financial stability. In order to maintain Apple’s leading position in the technology industry, continuous innovation and market expansion are necessary.